Mass Spectrometric Analysis Identifies AIMP1 and LTA4H as FSCN1‐Binding Proteins in Laryngeal Squamous Cell Carcinoma. Issue 21 (26th July 2019) - Gao, Wei; An, Changming; Xue, Xuting; Zheng, Xiwang; Niu, Min; Zhang, Yuliang; Liu, Hongliang; Zhang, Chunming; Lu, Yan; Cui, Jiajia; Zhao, Qinli; Wen, Shuxin; et al.
Abstract: Dysregulation of fascin actin‐bundling protein 1 (FSCN1) enhances cell proliferation, invasion, and motility in laryngeal squamous cell carcinoma (LSCC), while the mechanism remains unclear. Here, co‐immunoprecipitation and mass spectrometry is utilized to identify potential FSCN1‐binding proteins. Functional annotation of FSCN1‐binding proteins are performed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis. Furthermore, the protein–protein interaction network of FSNC1‐binding proteins is constructed and the interactions between FSCN1 and novel identified interacting proteins AIMP1 and LTA4H are validated. Moreover, the expression and functional role of AIMP1 and LTA4H in LSCC are investigated. A total of 123 proteins are identified as potential FSCN1‐binding proteins, and functional annotation shows that FSCN1‐binding proteins are significantly enriched in carcinogenic processes, such as filopodium assembly‐regulation and GTPase activity. Co‐IP/western blotting and immunofluorescence confirm that AIMP1 and LTA4H bind and colocalize with FSCN1. Furthermore, both AIMP1 and LTA4H are upregulated in LSCC tissues, and knockdown of AIMP1 or LTA4H inhibits LSCC cell proliferation, migration, and invasion. Collectively, the identification of FSCN1‐binding partners enhances understanding of the mechanism of FSCN1‐mediated malignant phenotypes, and these findings indicate that FSCN1 binds to AIMP1 and LTA4H might promote the progression of LSCC.